ANALISIS FAKTOR-FAKTOR PENERIMAAN OPINI AUDITOR DENGAN MODIFIKASI GOING CONCERN (Studi Empiris di Bursa Efek Indonesia) - Gama, Angga Patria; Astuti, Sri (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 9 No 1 (2014), 2014)
ABSTRACT This research aimed to determine the effect of audit quality, prior year auditor’s opinion, company growth, company size, audit delay, and the expertise of audit committee on the acceptance of auditor’s opinion with going concern modification, both simultaneously and partially. This research used secondary data obtained from the annual reports published on the official website of the Indonesia Stock Exchange www.idx.co.id. Samples were companies listed on Indonesia Stock Exchange from 2008 – 2011. This research used purposive sampling and obtained 1.143 observation data. The hypotheses were examined using logistic regression. Results of simultaneous test showed that audit quality, prior year auditor’s opinion, company growth, company size, audit delay, and the expertise of audit committee significantly influenced the acceptance of auditor’s opinion with going concern modification. Partial test results indicated that prior year auditor’s opinion, company size, and audit delay significantly influenced the acceptance of auditor’s opinion with going concern modification, while audit quality, company growth, and the expertise of audit committee did not significantly influence the acceptance of auditor’s opinion with going concern modification. Keywords: auditor, audit opinion, going concern